2013
DOI: 10.1016/j.bmc.2013.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological evaluation, X-ray molecular structure and molecular docking studies of RGD mimetics containing 6-amino-2,3-dihydroisoindolin-1-one fragment as ligands of integrin αIIbβ3

Abstract: A series of novel RGD mimetics containing phthalimidine fragment was designed and synthesized. Their antiaggregative activity determined by Born's method was shown to be due to inhibition of fibrinogen binding to αIIbβ₃. Molecular docking of RGD mimetics to αIIbβ₃ receptor showed the key interactions in this complex, and also some correlations have been observed between values of biological activity and docking scores. The single crystal X-ray data were obtained for five mimetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Two data sets have been collected from literature sources and in-house studies: (1) the affinity data set comprising 338 compounds with reported affinity values for α IIb β 3 and (2) the antiaggregation activity data set comprising 453 compounds tested under similar conditions. These data sets were used for the development of QSAR and ligand-based pharmacophore models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two data sets have been collected from literature sources and in-house studies: (1) the affinity data set comprising 338 compounds with reported affinity values for α IIb β 3 and (2) the antiaggregation activity data set comprising 453 compounds tested under similar conditions. These data sets were used for the development of QSAR and ligand-based pharmacophore models.…”
Section: Resultsmentioning
confidence: 99%
“…The acid 1 has been synthesized using a previously published method . The optically active α-sulfonamido-β-alanines were prepared from l - or d -asparagine using previously published methods. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4.Why, during the configuration of isomerization, does the enantiomer not always pass through an achiral boundary? Antiviral activity, antimicrobial activity and antitumor activity Pharmacokinetic Parameter [25], [41][42][43][44][45] Affinity for different biological targets [46][47][48][49][50][51][52][53] Different types of toxicity [44], [54][55][56][57][58][59][60][61][62][63][64][65]…”
Section: The Methodology Of Sirmsmentioning
confidence: 99%
“…Phthalimide is an aromatic imide with two carbonyl groups bounded to amine moiety and used in organic synthesis for the preparation of a wide variety of compounds with different substituents in both the aromatic ring and the nitrogen atom. These compounds are attractive for their biological activities (Sharma et al, 2010) among them, as antibacterial, antifungal, antimicrobial, anticancer (Ahmed et al, 2016; Akgün et al, 2012; Santos et al, 2009; Tandon et al, 2009; Wang et al, 2013), as platelet aggregation, tryptase inhibitors (Krysko et al, 2013; Tetsuhashi et al, 2010), anti‐inflammatory and immunomodulatory prototypes (Leite et al, 2014), hypolipidemic activity (El‐Zahabi et al, 2012), antiangiogenic activity (Nagarajan et al, 2013), and HDAC's inhibitors (Lee et al, 2007; Shinji et al, 2005, 2006).…”
Section: Introductionmentioning
confidence: 99%